Effect of integrated safety program on safety behaviors among rice farmers: A quasi-experimental study - Anon Wisutthananon (2020)
© 2019, Thailand Nursing and Midwifery Council. All rights reserved. Unsafe working behaviors are considered the most important determinants of injuries among rice farmers. This quasi-experimental study examined the effect of an integrated safety program for enhancing safety behaviors among rice farmers. Two districts in a province in Northern Thailand were purposively selected and randomly assigned to be the experimental and control groups. Eighty-two farmers from two districts were purposively selected according to the criteria and matching equally for each group. The experimental group only received the integrated safety program which comprised awareness raising, working behavior modification, and a supportive environment. Safety behaviors were measured by a structured questionnaire. Data were analyzed using descriptive statistics and two-way repeated measures analysis of variance (ANOVA). Results revealed that the participants in the experimental group had statistically significant higher mean scores of safety behaviors that included safe pesticide use, personal protective equipment use, and compliance with safety rules and regulations, than those in the control group across all time points of measurement at weeks 8 and 12 after during follow-up. Thus, this safety intervention could be useful for nurses and occupational health professionals, and health promoters to enhance safety behaviors among rice farmers and thus reduce farmer morbidity and mortality due to unsafe work practices.